Десорбция капель водных растворов солей LiBr, CaCl2, LiCl, NaCl; Неделя науки СПбПУ; Ч. 1 - Исламова А. Г. Анастасия Гомильевна; Орлова Е. Г. Евгения Георгиевна; Феоктистов Д. В. Дмитрий Владимирович; Мисюра С. Я. Сергей Яковлевич (2016, 2016)
Заглавие с экрана